2020
DOI: 10.1080/03057925.2020.1749993
|View full text |Cite
|
Sign up to set email alerts
|

Are children with disabilities in school and learning? Evidence from a household survey in rural Punjab, Pakistan

Abstract: Invisibility of children with disabilities in data on educational access and learning is a key policy challenge for tracking progress towards the Sustainable Development Goals. In this article, we report findings from a household survey undertaken in rural Punjab, Pakistan. These data enable us to identify the extent to which children with disabilities are in school and learning the basics in literacy and numeracy. We find that, perhaps contrary to expectations, many of these children in this context are in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The only exception is the study by Bakhshi, Babulal, and Trani (2018) from Sudan [ 6 ]. The other few earlier papers in the developing context are mainly from Asia, with the study of Takeda and Lamichhane (2018) from India [ 24 ], Malik et al (2020) and Singal et al (2020) from Pakistan [ 25 , 26 ]. Most studies have applied the Washington Group definition of disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only exception is the study by Bakhshi, Babulal, and Trani (2018) from Sudan [ 6 ]. The other few earlier papers in the developing context are mainly from Asia, with the study of Takeda and Lamichhane (2018) from India [ 24 ], Malik et al (2020) and Singal et al (2020) from Pakistan [ 25 , 26 ]. Most studies have applied the Washington Group definition of disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies simply use univariate analysis while including the disability status [ 15 , 21 ]. Some studies dichotomise the indicators (able to read or write) for school performance and use logistic or probit models [ 6 , 25 ]. Takeda and Lamichhane (2018) use an OLS model to estimate school performance as a continuous score [ 24 ].…”
Section: Data Methods and Estimation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of developing and putting into practice policies that would give affect the "UN Convention on the Rights of Persons with Disabilities", governments are required to gather pertinent information, including statistical and research data (UNCRPD). The SDGs also stress the importance of providing comprehensive, current, and trustworthy data that is divided into categories based on unfavourable statuses, such as handicap, and other criteria (Malik et al 2022).…”
Section: Research Question Of the Studymentioning
confidence: 99%
“…The Annual Status of Education Reports (ASER- Pakistan, 2017) examined extensive disparities between richer and poorer cities in rural Pakistan and, even within the richest cities, it was found that poor girls perform unsatisfactory more often than their richer counterparts (Alcott & Rose, 2015). ASER also presented emerging evidence on both access and learning for children with disabilities in the Punjab province in Pakistan (Malik et al, 2022). Many children with diverse needs are learning the fundamentals in numeracy and literacy, although their chances of learning the basics are more constrained compared with their peers in a context of overall very low levels of learning.…”
mentioning
confidence: 99%